2011
DOI: 10.1063/1.3551464
|View full text |Cite
|
Sign up to set email alerts
|

Fast numerical treatment of nonlinear wave equations by spectral methods

Abstract: A method is presented that accelerates spectral methods for numerical solution of a broad class of nonlinear partial differential wave equations that are first order in time and that arise in plasma wave theory. The approach involves exact analytical treatment of the linear part of the wave evolution including growth and damping as well as dispersion. After introducing the method for general scalar and vector equations, we discuss and illustrate it in more detail in the context of the coupling of high-and low-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Other wave packets analyzed during multiple strong turbulence runs with the 3D electromagnetic simulation code of Skjaeraasen et al [2011] yield almost identical results (not shown). In the earlier stages of collapse the electric fields of wave packets cannot be clearly distinguished from the background Langmuir waves; however, the radial functions of these packets tend to be better fitted by the Gaussian than the Lorentzian potential.…”
Section: Collapse Theorymentioning
confidence: 65%
“…Other wave packets analyzed during multiple strong turbulence runs with the 3D electromagnetic simulation code of Skjaeraasen et al [2011] yield almost identical results (not shown). In the earlier stages of collapse the electric fields of wave packets cannot be clearly distinguished from the background Langmuir waves; however, the radial functions of these packets tend to be better fitted by the Gaussian than the Lorentzian potential.…”
Section: Collapse Theorymentioning
confidence: 65%
“…Equation 3is currently solved by neglecting collisional absorption, pump depletion, and nonlinear terms (i.e., trivially), while Eqs. 4and 5are advanced by a pseudospectral method: 62,63 All the linear propagation terms of Eqs. 4and 5are computed in Fourier space (Landau damping can be easily written in k space), while the nonlinear term in Eq.…”
Section: The Extended Quasi-linear Zakharov (Qzak) Model Of Tpdmentioning
confidence: 99%
“…[7] We solve the Zakharov equations in three dimensions on a 128 3 grid with dimensions of (1200 D ) 3 , using the code in Graham et al [2011]. The numerical integration is optimized using the phase-removal scheme of Skjaeraasen et al [2011]. In our simulations, damping is applied to Langmuir waves at all k at a rate 0 = -6 10 -4 !…”
Section: Simulations Of Truncated Backscattermentioning
confidence: 99%
“…The numerical integration is optimized using the phase-removal scheme of Skjaeraasen et al [2011]. In our simulations, damping is applied to Langmuir waves at all k at a rate 0 = -6 10 -4 !…”
Section: Simulations Of Truncated Backscattermentioning
confidence: 99%